2009
DOI: 10.1364/oe.17.019093
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ultrafast optical nonlinearity of porous anodized aluminum oxide nanostructures

Abstract: Enhanced ultrafast optical nonlinearities of porous anodized aluminum oxide (AAO) nanostructures, well-known templates for quantum dots fabrication, have been investigated using the differential optical Kerr gate technique at 800 nm. The optical nonlinearity is strongly influenced by the pore number density, the pore size and the shape. Large values of the third-order nonlinear optical susceptibility (chi((3))) of the order of 10(-10)esu are measured. The nonlinear response time is faster than or comparable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The porosity was highest in ZnO1 films, which leads to the inference that largest χ (3) value observed for ZnO1 in ps/fs measurements is, possibly, a consequence of its denser microstructure. Similar results were obtained in porous Al oxide nanostructures [70] wherein they demonstrated that the local electric field enhancement was due to pore size, pore shape, and surface state effects which in turn enhanced the optical nonlinearity [69]. Han et al [9] reported β values of 1.1 cm MW −1 for ZnO films annealed at 950-1050°C and attributed the increased nonlinearity due to the interfacial state enhancement.…”
Section: Samplesupporting
confidence: 58%
See 1 more Smart Citation
“…The porosity was highest in ZnO1 films, which leads to the inference that largest χ (3) value observed for ZnO1 in ps/fs measurements is, possibly, a consequence of its denser microstructure. Similar results were obtained in porous Al oxide nanostructures [70] wherein they demonstrated that the local electric field enhancement was due to pore size, pore shape, and surface state effects which in turn enhanced the optical nonlinearity [69]. Han et al [9] reported β values of 1.1 cm MW −1 for ZnO films annealed at 950-1050°C and attributed the increased nonlinearity due to the interfacial state enhancement.…”
Section: Samplesupporting
confidence: 58%
“…Porosity is the property of materials which affects the nonlinear optical response at nanoscale. Earlier studies have indicated that nanoporous Si [69], aluminum oxide nanostructures [70] exhibited large χ (3) values depending on the pore structure, size, and density. In the case of our samples ZnO1 had well sorted pores, compared to others, probably resulting in a higher χ (3) for ZnO1.…”
Section: Samplementioning
confidence: 99%
“…The total χ ð3Þ of Au-Ni-Au nanorod arrays under an incident angle of 01 is 2:32 Â 10 À 6 esu. In addition, the value of Im χ ð3Þ of AAO template is 1:58 Â 10 À 11 esu, [18] which can be neglected compared with that of nanorods.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrafast low-power all-optical switching has been experimentally realized in a photonic crystal based on a nanocomposite material consisting of silver nanoparticles in a π -conjugated polymer [99]. Enhanced ultrafast optical nonlinearity has been studied in anodized aluminum oxide nanostructures as a function of the pore number density and pore diameters [100]. A strong enhancement of the third-order susceptibility has been observed in an array of rectangular gold nanoparticles and attributed to a strong electric field localization [101].…”
Section: Experimental Studiesmentioning
confidence: 99%